Identification of Pathogens Causing Important Diseases in Leatherleaf Fern (Rumohra adiantiformis) and In Vitro Inhibition using Bacillus velezensis B-27 - Barokati Tsaniyah; Tri Joko; Ani Widiastuti (Universitas Sebelas Maret, 2024)
Leatherleaf fern (Rumohra adiantiformis) is a famous ornamental-leaf plant that has been used by florist entrepreneurs around the world. It is one of the leading export commodities in Indonesia, however, currently, there are some diseases of this leaf reported in the field causing yield loss and reducing the economic value. This study aimed to identify the pathogens causing the recent 3 significant diseases of leatherleaf fern, including leaf blight, leaf tip rot, and post-harvest leaf rot, and in vitro analysis of beneficial bacteria, Bacillus velezensis B-27, against the pathogens. The methods used in this study were isolation, pathogenicity test, morphological observation, molecular identification of pathogens, and poisoned food technique of B. velezensis against those pathogens compared to fungicides and bactericides. The results of molecular identification showed that Neopestalotiopsis sp. and Pantoea ananatis caused leaf blight, Fusarium oxysporum f. sp. sesami triggered leaf tip rot, while Calonectria sp. and P. ananatis contributed to post-harvest leaf rot. Based on in vitro analysis, B. velezensis B-27 reduced the growth of the Neopestalotiopsis sp. DM C with the highest inhibition of 95.6%, Neopestalotiopsis sp. DM B with 84.3%, F. oxysporum f. sp. sesami with 61.9%, Calonectria sp. with 93.4%, and inhibited the growth of P. ananatis by producing a clear zone. This research concludes that B. velezensis B-27 has the potential as a biocontrol against pathogens causing significant diseases in leatherleaf ferns due to its ability to inhibit pathogens and its advantage as a beneficial microbe that is environmentally friendly to support sustainable agriculture.